Molecular changes in gelatin aging observed by NIR and fluorescence spectroscopy. (December 2016) - Duconseille, Anne; Andueza, Donato; Picard, Fabienne; Santé-Lhoutellier, Véronique; Astruc, Thierry
Abstract: The pharmaceutical industry requires a narrow variability in gelatin properties during storage to meet strict quality standards for hard capsules. To test the properties of gelatin during shelf life, gelatin is aged in high temperature and high humidity conditions. These conditions induce the formation of cross-links in gelatin chains that impact its chemical composition and thereby the properties of the capsules. Non-aged and aged pig skin gelatins were analyzed in raw granule or powder forms by near-infrared and fluorescence spectroscopy to elucidate the mechanisms of cross-link formation during aging. Both near-infrared and fluorescence spectroscopy clearly separated non-aged from aged samples. Aging induced the formation of dityrosine and other cross-links involving amine and aldehyde functions. The presence of 3, 4-dihydroxyphenylalanine (DOPA), a fluorescent product of tyrosine oxidation involved in cross-link formation, was evidenced in gelatin. Graphical abstract: Highlights: Gelatin aging is highlighted by both Fluorescence and NIR spectroscopies. Dityrosine bonds are highly suspected to be formed in gelatin during aging. Amines and aldehydes are likely to form cross-links during gelatin aging. Gelatin aging induces DOPA chemical and/or structural environment changes.